2020
DOI: 10.1186/s13046-020-01577-z
|View full text |Cite
|
Sign up to set email alerts
|

SH3BGRL confers innate drug resistance in breast cancer by stabilizing HER2 activation on cell membrane

Abstract: Background: HER2-positive breast cancer is usually associated to the more aggressive progression and the worse prognosis, but the mechanism underlying the innate resistance to HER2-targeted therapy remains elusive. The scaffold protein SH3-domain-binding glutamic acid-rich protein-like protein (SH3BGRL) is indicated as a tumor suppressor in some cancers, but it is highly expressed in breast cancers. Here we characterized the tumorigenic function of SH3BGRL in HER2-expressing breast cancer cells and the subsequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…The scaffold protein SH3BGRL, observed, plays an important role in signal transduction, membrane transport, cytoskeleton rearrangement, and protein-protein interactions in other key cellular processes. The expression level of SH3BGRL is also considered a diagnostic index of breast cancer [37,38]. PCMTD1 is used as a potential passenger gene in EC [39].…”
Section: Discussionmentioning
confidence: 99%
“…The scaffold protein SH3BGRL, observed, plays an important role in signal transduction, membrane transport, cytoskeleton rearrangement, and protein-protein interactions in other key cellular processes. The expression level of SH3BGRL is also considered a diagnostic index of breast cancer [37,38]. PCMTD1 is used as a potential passenger gene in EC [39].…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, SH3BGRL is shown to be overexpressed in various types of breast cancers, including BRCA1 mutant, ESR/ER-positive, triple-negative and lymphocytic infiltration-positive breast tumors by proteomics analysis [ 60–62 ], suggesting its possible tumor-promoting role. Recently, we found that SH3BGRL renders innate ERBB2/HER2-targeting drug resistance in breast cancer [ 63 ]. In contrast to this oncogenic character, SH3BGRL is shown as an inhibitor of REL/v-Rel-induced transformation in chicken cells [ 64 ] and a suppressor in leukemogenesis [ 65 ] and triple-negative breast cancer cells [ 66 ].…”
Section: Introductionmentioning
confidence: 99%
“…The DELs upstream of POU3F4 were also located downstream of SH3BGRL. SH3BGRL was reported to play a role in gastric cancer, acute myeloid leukemia and breast cancer [30][31][32]. However, whether DELs located between POU3F4 and SH3BGRL genes in uence the function of SH3BGRL remains unknown.…”
Section: Discussionmentioning
confidence: 99%